EVALUASI PENENTUAN LOKASI PERUMAHAN DI WILAYAH GEDEBAGE KOTA BANDUNG - Hilman, Maman (-)
This research aimed at understanding of housing location determination over the areas of Gedebage, Bandung City. The evaluation is based on physical conditions of the environment and socioeconomic conditions, by comparing existing conditions of the housing with established standards. The findings are: (i) Batununggal (B1) in Bandung Kidul Sub-District belongs to suitable category of housing location, (ii) Mengger (B3) in Bandung Kidul Sub-District belongs to unsuitable category of housing location, (iii) Sekejati (M3) in Margacinta Sub-District belongs to suitable category of housing location; (iv) Cisaranten Kidul (R4) at Rancasari Sub-District belongs to adequately suitable category of housing location; and (iv) Cisaranten Kidul (R2) at Rancasari Sub-District belongs to adequately suitable housing location.Keywords: Evaluation, housing locations